Conservation status of flora and fauna in the nickel mining area of PT Hengjaya Mineralindo - Muchtazar, Muchtazar; Cahyono , Harry; Lelono , Virgo; Lestari , Firda (Gema Wiralodra, 2024)
Indonesia is an archipelagic country with a high level of biodiversity from the sea to the mountains. Likewise, the island of Sulawesi has a variety of endemic flora and fauna with an extraordinary level of endemicity. This rich flora and fauna face various threats that cause ecosystem degradation. This research is intended to review the level of flora and fauna status in the Sulawesi region, especially in the PT Hengjaya Mineralindo mining area in Bungku Pesisir and Bahodopi District, Central Sulawesi. Based on observations in areas with code HA WD 06, HA Pit Central, HA Arboretum 1 and HA Arboretum 2 areas, it was found that some flora and fauna were categorized as being in conservation status by Minister of Environment and Forestry Regulation No. P 106 Concerning Protected Plants and Animals, International Union for Conservation of Nature (IUCN), and the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Thus, the company will always strive to encourage ecological succession to achieve ecosystem stability in the future through sustainable practices.